Clinical inertia in insulin prescription for patients with type 2 diabetes mellitus among family physicians in Saudi Arabia - Surrati, Amal M. Qasem; Alshanqiti, Asma; Albadrani, Muayad; AlHarbi, Mansour; Tobaiqi, Muhammad Abu Baker (Journal of the Pakistan Medical Association, 2025)
Objective: To explore the knowledge and perceptions of primary care physicians about clinical inertia in the management of type 2 diabetes, and to identify the contributing factors. Method: The cross-sectional study was conducted in Madinah, Saudi Arabia between April and May 2020, and comprised qualified doctors work in primary care centres as general practitioners or board-certified family physicians. Data was collected using a questionnaire on participants’ demographics, knowledge and practices related to diabetes management, and their perceptions regarding clinical inertia in the management of type 2 diabetes. The questionnaire was distributed online. Data was analysed using SPSS 28. Results: Of the 250 subjects approached, 200 (80%) completed the questionnaire; 105(52.5%) males and 95(47.5%) females. There were 78 (39%) subjects aged 41-50 years. Overall, 90(45%) subjects were general practitioners, 41(20.5%) were family medicine specialists, and 62(31%) were family medicine consultants. Of the total, 96(48%) respondents were aware of the concept of therapeutic inertia. Factors contributing to inertia were identified at the patient, physician and system levels. Physician-related factors included concern about hypoglycaemia 129(64.5%), complexity of treatment 111(55.5%), and patient refusal 67(33.5%). Patient-related barriers were resistance to lifestyle modifications 132 (66.0%), fear of weight gain 105(52.5%), and fear of injections 101(50.5%). System-level barriers included lack of multidisciplinary teams 137(68.5%), time constraints 107 (53.5%), and high workload 104(52.0%). A significant association was found between professional classification and awareness of therapeutic inertia (p<0.05). Conclusion: Addressing barriers at the physician and system levels could help reduce clinical inertia in insulin prescription, potentially leading to improved diabetes outcomes. Key Words: Type 2 diabetes, Diabetic therapeutic inertia, HbA1c, Primary care, Physicians, Clinical inertia.